Three Novell Analog-Domain Algorithms for Motion Detection in Video Surveillance. (18th January 2011) - Verdant Verdant, Arnaud Arnaud; Villard Villard, Patrick Patrick; Dupret Dupret, Antoine Antoine; Mathias Mathias, Hervé Hervé
Abstract : As to reduce processing load for video surveillance embedded systems, three low-level motion detection algorithms to be implemented on an analog CMOS image sensor are presented. Allowing on-chip segmentation of moving targets, these algorithms are both robust and compliant to various environments while being power efficient. They feature different trade-offs between detection performance and number of a priori choices. Detailed processing steps are presented for each of these algorithms and a comparative study is proposed with respect to some reference algorithms. Depending on the application, the best algorithm choice is then discussed.